Upaya Meningkatkan Hasil Belajar Keterampilan Shooting Permainan Sepakbola Melalui Model Pembelajaran Snowball Throwing Siswa SMA Negeri 11 Muaro Jambi - Vandini, Sekar Satya; Nugraha, Ugi; Yanto, Anggel Hardi (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aimed to enhance learning outcomes in shooting skills for soccer through the implementation of the Snowball Throwing learning model among Grade X students at SMA Negeri 11 Muaro Jambi. The research methodology employed was Classroom Action Research (CAR) conducted over two cycles, involving 35 students as subjects. Initial observations revealed that students' shooting skills were below satisfactory levels, evidenced by an average score of 60 and only 34% of students achieving the Minimum Mastery Criteria (KKM) of 75. Following the implementation of the Snowball Throwing model, significant improvements in students' shooting abilities were observed. In the first cycle, the average score increased to 78 with a 66% mastery rate, while in the second cycle it rose to 91 with mastery reaching 91%. The Snowball Throwing model proved effective in promoting active student engagement, enhancing comprehension of shooting techniques, and fostering a more interactive learning environment. The research findings recommend the adoption of active learning models such as Snowball Throwing in physical education instruction to improve students' motor skills development.